2011
DOI: 10.1158/1078-0432.ccr-10-1890
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Derived Neurotrophic Factor and Neurotrophin-4/5 Are Expressed in Breast Cancer and Can Be Targeted to Inhibit Tumor Cell Survival

Abstract: Purpose: Given that nerve growth factor has previously been shown to be involved in breast cancer progression, we have tested here the hypothesis that the other neurotrophins (NT) are expressed and have an influence in breast tumor growth.Experimental Design: The expression of brain-derived neurotrophic factor (BDNF), NT-3 and NT-4/5, as well as the neurotrophin receptor p75 NTR , TrkB, and TrkC, was studied by RT-PCR, Western blotting, and immunohistochemistry in cell lines and tumor biopsies. The biological … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
108
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(120 citation statements)
references
References 41 publications
7
108
1
Order By: Relevance
“…Mice inoculated with breast cancer cells and treated with antibodies against BDNF display slower tumor progression compared to mice treated with control antibodies (38). These results were recapitulated in a mouse model of uterine sarcoma (39) and neuroblastoma (40,41).…”
Section: Bdnf: a Governor Of Chemotherapeutic Sensitivitymentioning
confidence: 68%
“…Mice inoculated with breast cancer cells and treated with antibodies against BDNF display slower tumor progression compared to mice treated with control antibodies (38). These results were recapitulated in a mouse model of uterine sarcoma (39) and neuroblastoma (40,41).…”
Section: Bdnf: a Governor Of Chemotherapeutic Sensitivitymentioning
confidence: 68%
“…ProNGF production adds to the recently reported expression of brain-derived neurotrophic factor (BDNF) and neurotrophin-4/5 (NT-4/5), showing that neurotrophin family members and their receptors are generally involved in breast cancer (35). Brain-derived neurotrophic factor and NT-4/5 exhibit a different type of activity on breast cancer cells as they were found to stimulate tumor cell survival.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies on breast and ovarian cancer cells have suggested that BDNF/TrkB stimulates cell survival and migration (20,22,23,25). BDNF is likely not to enhance viability since the BDNF/TrkB pathway is already activated at its optimal level by BDNF secreted from the cells as an autocrine factor.…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, BDNF expression has been shown to be higher in tumor samples compared to non-neoplastic tissues, while BDNF transcript levels have been associated with unfavorable pathological parameters and adverse clinical outcomes (24). Moreover, BDNF has been shown to induce resistance to apoptosis in breast cancer cells, while injection of an anti-BDNF antibody has been proven to reduce the growth of breast tumors xenografted in mice (25). The present study aimed to explore the effects of GRPR and TrkB ligands on the viability of human breast, ovarian and cervical cancer cells in vitro.…”
Section: Introductionmentioning
confidence: 99%